Deteksi Gen B1 sebagai Penanda Toxoplasmosis pada Wanita Usia Subur di Kabupaten Bandung Barat - Naully, Patricia Gita; Supendi, Selvi Anggraeni (POLTEKKES KEMENKES YOGYAKARTA, 2020)
Congenital toxoplasmosis can cause damage and death to the fetus, to prevent this case, toxoplasmosis testing is important for the woman of childbearing age. One of the methods to screening the presence of T. gondii in the blood is Polymerase Chain Reaction (PCR). One of the T. gondii genes which can be used as a marker is the B1 gene. There are many toxoplasmosis cases in Indonesia, but the data is still difficult to find in West Bandung Regency. This study aimed to determine the number of toxoplasmosis cases in a woman of childbearing age in West Bandung Regency using the B1 gene as a marker and to determine the factors that influence these cases by conducting statistical analysis on the results of the questionnaire. The sample used in this study was 50 women of childbearing age (got married and domiciled in West Bandung). All samples have met the inclusion criteria and signed the informed consent. DNA from blood specimens was isolated using the Wizard Genomic DNA Purification Kit. The concentration and purity of isolated DNA were measured using a nanodrop device. Besides, the B1 gene from T. gondii was amplified using a pair of specific primers and visualized by the agarose electrophoresis method. Data were analyzed using the logistic regression method. The results showed that 7 women of childbearing age women (14%) in West Bandung Regency had toxoplasmosis. Frequent contact with pets, especially cats, was a significant factor (p <0.005) in this disease transmission.